Overview of the Boston Retinal Prosthesis: Challenges and Opportunities to Restore Useful Vision to the Blind - Rizzo, Joseph F. (Conf Proc IEEE Eng Med Biol Soc, 2011)
A small, hermetic, wirelessly-controlled retinal prosthesis was developed for pre-clinical studies in Yucatan mini-pigs. The device was implanted on the outside of the eye in the orbit, and it received both power and data wirelessly from external sources. The prosthesis drove a sub-retinal thin-film array of sputtered iridium oxide stimulating electrodes. The implanted device included a hermetic titanium case containing the 16-channel stimulator chip and discrete circuit components. Feedthroughs in the hermetic case connected the chip to secondary power- and data-receiving coils, which coupled to corresponding external power and data coils driven by a power amplifier. Power was delivered by a 500 KHz carrier, and data were delivered by frequency shift keying. Stimulation pulse strength, duration and frequency were programmed wirelessly from an external computer system. Through an ‘outbound’ telemetry channel, electrode impedances were monitored by an on-board analog to digital converter that sampled the output voltage waveforms. The final assembly was tested in vitro in physiological saline and in vivo in two mini-pigs for up to three months by measuring stimulus artifacts generated by the implant’s current drivers.